Africa: geopolitics of the populations of a continent with ever-increasing demographic weight - (:unkn) unknown (My University, 2023)
The knowledge of the characteristics of the dynamics of the settlement and the natural and migratory movements of Africa acquired then makes it possible to pre-sent certain aspects of the geopolitics of the African populations, that is to say those resulting from the law of the number and the law of the diasporas.
Keywords: African Research